BRIDGING THE BRAIN AND BLOOD: THE LINK BETWEEN EEG FINDINGS AND SERUM FERRITIN LEVELS IN PAEDIATRIC FEBRILE SEIZURES. - Dr. Shubham S. Jadhav; Dr. Swati S. Jagtap (Journal of Population Therapeutics and Clinical Pharmacology, 2024)
Introduction: Febrile seizures and Iron deficiency anaemia are common diseases in developing countries. Iron deficiency is known to cause neurological and behavioural changes, attention and learning deficit. Therefore, this study is performed to find out EEG changes and serum ferritin levels in children with febrile seizures(n=51). Study design: Cross-sectional study. Methods: Patients with febrile seizure of age group 6 months to 5 years visiting OPD and admitted under Paediatric Department, KIMSDU Karad were included in this study. EEG was performed using Clarity 16 channel EEG machine under sedation after proper hair wash. Blood samples were collected for estimation of serum ferritin, haemoglobin, MCV, MCH, MCHC levels. Serum ferritin was estimated by using TOSOH AIA 360 machine in department of Biochemistry KIMSDU, Karad. Hb, MCV, MCH, MCHC were estimated using NIHON KOHDEN celtac alpha automated hematology blood analyser in department of Pathology KIMSDU, Karad. EEG and haematological parameters were analysed. Results: Epileptiform activity in EEG was observed in 31 out of 51 patients (60.8%). Those patients who had Epileptiform activity in EEG had significantly lower Serum Ferritin (p=0.002) and MCV values (p=0.043). No statistically significant difference were observed in Hb, MCH and MCHC in patients with and without epileptiform activity in EEG. Conclusions: Patients with reduced levels of serum ferritin and MCV showed epileptiform activity in EEG recordings. It is necessary to treat and have regular follow ups in these patients, to find out the persistence of epileptiform activity.